(untitled) (JISTECH: Journal of Information Science and Technology, 2024)
The hymn of praise Seruling Emas and Suara Gembira is one of the hymns or songs used by Christians, specifically in the GKI Church throughout Papua, including the congregation of GKI Maranatha Biak, in the worship process. However, the system of using hymn books/papers is still ineffective and inefficient. Therefore, this research aims to develop a practical, effective, and efficient hymn application for the congregation, which helps facilitate information delivery and saves costs in creating or text of joyous sound songs. The methods of data collection include observation, interviews, and literature studies. The application development uses the waterfall method or model, through stages of analysis, design, implementation using the Flutter Framework, and testing. The result is an Android-based application "Kidung Pujian Seruling Emas dan Suara Gembira" successfully created using the Flutter Framework. This application has a menu featuring a list of songs with several features including text/lyrics and instrumental audio. The application testing is done using the BlackBox method, and the results of the testing show good results, meeting the specified specifications, and expected to help the congregation obtain accurate information.